1970
DOI: 10.3329/bjsir.v41i1.267
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nutritional Quality of Cabbage as Affected by Nitrogen and Phosphorus Fertilization

Abstract: An experiment was conducted in field condition to study the effect of nitrogen-phosphorus fertilization on growth, yield and nutrient content of cabbage. The experiment was laid out in randomize block design with three replications. The yield and yield components were maximized by N3P2 fertilizer treatment. Nutrient content of cabbage varied with fertilizer treatment. The maximum amount of reducing sugar, ascorbic acid, phosphorus were found at the highest rate of N - P fertilization whereas accumulation of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 2 publications
3
19
1
1
Order By: Relevance
“…(Khan, F., Khan, T., Namatullah, & Tajudin, 2015). Haque et al (2006) recorded an increase in head diameter of cabbage that had occurred with an increase in the use of N and P fertilizers.…”
Section: Yield Of Head Cabbagementioning
confidence: 99%
“…(Khan, F., Khan, T., Namatullah, & Tajudin, 2015). Haque et al (2006) recorded an increase in head diameter of cabbage that had occurred with an increase in the use of N and P fertilizers.…”
Section: Yield Of Head Cabbagementioning
confidence: 99%
“…No campo, a fertilização com N aumenta a produção (Huang et al, 2004;Aquino et al, 2005a;Din et al, 2007) e otimiza a qualidade de repolho (Aquino et al, 2005b;Haque et al, 2006). Escassez de N pode resultar em baixa produtividade e cabeças menores, por causa da reduzida área foliar (Cardoso & Hiraki, 2001;Torres et al, 2003).…”
Section: Introductionunclassified
“…Several studies have been reported that concern N doses for cabbage plants, including Khan et al (2002), Aquino et al (2005aAquino et al ( , 2005b, Ekbladh et al (2007), Haque et al (2006), Machado et al (2006); Aquino et al (2009);Moreira et al (2011). However, none of these investigations analyzed the accumulation of macronutrients by cabbage plants as influenced by the plant population and N doses.…”
Section: Introductionmentioning
confidence: 99%